THE ROLE OF GREENPEACE INDONESIA IN ENCOURAGING THE JAKARTA PROVINCIAL GOVERNMENT TO ADDRESS AIR POLLUTION (2021–2023) - Shafiyah Kirana Putri; Muharjono, Muharjono (Paradigma: Jurnal Masalah Sosial, Politik, dan Kebijakan, 2025)
ABSTRACT Air pollution in Jakarta during the 2021–2023 period became an urgent environmental issue due to its direct impact on public health. In this context, Greenpeace Indonesia actively pushed the Provincial Government of DKI Jakarta to become more responsive, despite the absence of any formal cooperation agreement. This study aims to analyze the advocacy and campaign strategies used by Greenpeace Indonesia to influence public policy on air pollution control. Using a qualitative descriptive approach and Clive Archer’s theory of International Organizations, this research explores the interaction between Greenpeace Indonesia and the DKI Jakarta Government as non-state and state actors in the international system. The findings show that through digital campaigns, community engagement, and collaboration with academics and media, Greenpeace Indonesia effectively raised public awareness and exerted moral-political pressure on the DKI Jakarta Government. These findings affirm the vital role of civil society organizations in shaping environmental policy responses, particularly when formal mechanisms are absent. Keywords: Greenpeace Indonesia, air pollution, advocacy, DKI Government